2017
DOI: 10.1587/elex.14.20170537
|View full text |Cite
|
Sign up to set email alerts
|

Design of broadband inverse class-F power amplifier based on resistive-reactive series of inverse continuous modes

Abstract: In this paper, a resistive-reactive series of continuous inverse modes is proposed for extending bandwidth of the series of Inverse continuous mode (SICM). A broadband class inverse F power amplifier (PA), which operates across 2.5-4.1 GHz (48.5% bandwidth), is designed by using bare GaN HEMT to prove this theory. Experiment results indicate that the PA mentioned above is able to output 9.1-18.4 W saturation power and the drain efficiency can reach 47%-75% in the whole interested band. The average output power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In this paper, a phase-shifted current waveform is proposed to explore the design space of the SCIMs. The new current waveform contains resistive second harmonic components, and the corresponding impedance design space is different from the previous works [7,8]. So the proposed method offers an alternative solution for broadband applications.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In this paper, a phase-shifted current waveform is proposed to explore the design space of the SCIMs. The new current waveform contains resistive second harmonic components, and the corresponding impedance design space is different from the previous works [7,8]. So the proposed method offers an alternative solution for broadband applications.…”
Section: Introductionmentioning
confidence: 88%
“…Where I MAX is the saturated drain current, i dc ¼ 0:37, i 1 ¼ 0:43, i 3 ¼ 0:06, and À1 1 [5]. It can be found that the highest harmonic of the current expansion is the fourth harmonic instead of the fifth harmonic in [7,8], which is less complexity and more accurate for actual PA. In addition, the current waveforms remain unchanged as the parameter º varies.…”
Section: The Series Of Continuous Inverse Modes With Phase Shiftmentioning
confidence: 95%
See 1 more Smart Citation
“…Compact matching network is gradually taken more considerations. The traditional class-E [3,4,5,6,7,8,9,10,11,12], class-F [13,14,15,16,17,18,19,20,21], class-J [22,23,24,25] modes are high efficiency PA. Class-E works a strong drive and its theoretically efficiency can reach 100%, but its parallel capacitor cannot support the higher frequency band [26]. The class-F PA can solve the above issue, but it is designed in a narrow bandwidth with continuous mode less than an octave.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the class-J principle was extended to both the Class-F and inverse Class-F modes in the form of the continuous Class-F [9] and continuous inverse Class-F [10], respectively. To further expand the design space, several hybrid continuous modes and resistive-reactive continuous modes appreared in succession [11,12,13,14,15,16,17,18,19]. However, the design space of continuous modes mentioned above is derived at the current generate (I-gen) plane while the matching network is constructed at the package plane [20].…”
Section: Introductionmentioning
confidence: 99%